Local Antibiotic Therapy to Reduce Infection After Operative Treatment of Fractures at High Risk of Infection: A Multicenter, Randomized, Controlled Trial (VANCO Study). Issue 4 (April 2017) - O'Toole, Robert V.; Joshi, Manjari; Carlini, Anthony R.; Murray, Clinton K.; Allen, Lauren E.; Scharfstein, Daniel O.; Gary, Joshua L.; Bosse, Michael J.; Castillo, Renan C.
Abstract : Summary: A number of clinical studies in the spine literature suggest that the use of local vancomycin powder may substantially reduce surgical site infections (SSIs). These studies are primarily retrospective and observational and few focus on orthopaedic trauma patients. This study is a phase III, prospective, randomized, clinical trial to assess the efficacy of locally administered vancomycin powder in the prevention of SSI after fracture surgery. The primary goal of the VANCO Study is to compare the proportion of deep SSI 6 months after fracture fixation surgery. A secondary objective is to compare species and antibacterial susceptibilities among study patients who develop SSI. An additional objective is to build and validate a risk prediction model for the development of SSI. The study population consists of patients aged 18–80 years with tibial plateau or pilon (tibial plafond) fractures, at higher risk of infection, and definitively treated with plate and screw fixation. Participants are block randomized (within center) in a 1:1 ratio to either treatment group (local vancomycin powder up to a maximum dose of 1000 mg, placed immediately before wound closure) or control group (standard of care) for each study injury location, and return to the clinic for evaluations at 2 weeks, 3 months, and 6 months after fixation. The targeted sample size for the study is 500 fractures per study arm. This study should provide important information regarding the use of local vancomycin powder during the definitive treatment of lower extremity fractures and has the potential to significantly reduce the incidence of infection after orthopaedic trauma. Abstract : Supplemental Digital Content is Available in the Text.